Hunters Before ‘Diana’: examining pre-protohistoric lithic artifacts at the sanctuary of ‘Diana nemorensis’ (Lake Nemi, central Italy) as an indicator of human-environmental interaction - Flavio Altamura; Francesca Diosono (Studies in Ancient Art and Civilization)
The excavations of the Temple of Diana at Nemi (Lake Nemi, central Italy) from 2009 to 2021 yielded pre-protohistoric lithic artifacts. This information, combined with available geoarchaeological and palaeoenvironmental data, enables a reconstruction of lake level changes as well as human socio-economic and cultural activities in the area from the end of the Pleistocene to the Mid-Late Holocene. The results suggest that Epigravettian hunters occasionally exploited the basin area during the Final Palaeolithic. In the Early-Middle Holocene, rising water levels, reaching approximately 360 m above sea level, potentially hindered human occupation. However, during the Mid-Late Holocene, decreasing water levels allowed late prehistoric and protohistoric groups to engage in diverse activities in the basin, leaving traces that may hold early symbolic significance. The geomorphological setting and early occupation dynamics influenced the palaeoenvironmental conditions and the patterns of human presence and utilization of the area during the Iron Age and historical times.